GALERI SENI SEBAGAI INTERVENSI TERHADAP JAKARTA KOTA LAMA - Joseph Mulia; J.M. Joko Priyono Santoso (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The Kota Tua area, Tamansari District, West Jakarta is an area that is famous for its history. This area is not developing in the current era of modernization, thus making this area unattractive to visitors. To revive this area, it is necessary to intervene using the conservation conservation concept which aims to preserve the culture that has existed for a long time. The intervention was carried out by including a program of art galleries, educational areas, garden areas (public). To achieve success, data collection is carried out in the form of primary data such as site surveys, taking pictures from Google Maps and secondary data such as from journals, government publications and books. Next, an analysis process is carried out such as the needs in the area and the objectives to be achieved such as the preservation of the area contained in the form of buildings, historical items, paintings, sculptures and others, in addition to adding functions such as modern galleries that can attract attention. visitors to visit the building because it can be seen from the data that a modern gallery is a function that is currently developing. The analysis process results in art galleries dominating a larger space than other programs because their functions are in accordance with the objectives and can also solve problems. The final result of the intervention will only reach its maximum value if all systems in the Kota Tua area can be properly integrated. Keywords: Modernization; Regional Development; Urban Heritage; Visitors Abstrak Kawasan Kota Tua Kecamatan Tamansari, Jakarta Barat merupakan kawasan yang terkenal akan sejarahnya. Kawasan ini tidak berkembang di era modernisasi saat ini, sehingga membuat kawasan ini tidak diminati pengunjung. Untuk menghidupkan kawasan ini perlu dilakukan intervensi dengan menggunakan konsep konservasi preservasi yang bertujuan untuk melestarikan budaya yang sudah lama ada. Intervensi dilakukan dengan memasukkan program galeri seni rupa, area edukasi, area taman (publik). Untuk mencapai keberhasilan dilakukan pendataan dalam bentuk data primer seperti survei lokasi tapak,  pengambilan gambar dari google maps dan sekunder seperti dari jurnal, publikasi pemerintah maupun buku. selanjutnya dilakukan proses analisis seperti kebutuhan dalam kawasan tersebut dan tujuan yang akan dicapai seperti pelestarian kawasan yang tertuang dalam bentuk bangunan, barang-barang bersejarah, lukisan-lukisan, patung dan yang lain-lainnya, selain itu penambahan fungsi seperti galeri modern yang dapat menarik perhatian pengunjung untuk mengunjungi bangunan tersebut karena terlihat dari data juga galeri modern merupakan suatu fungsi yang sedang berkembang saat ini. Proses analisis menghasilkan galeri seni rupa mendominasi ruang lebih besar dibanding program-program lainnya dikarenakan fungsi yang sesuai dengan tujuan dan juga dapat menyelesaikan masalah. Hasil akhir intervensi baru akan mencapai nilai maksimal apabila seluruh sistem di dalam Kawasan Kota Tua dapat terintegrasi dengan baik.